Becoming an Engineer or a Lady Engineer: Exploring Professional Performance and Masculinity in Nepal's Department of Irrigation. Issue 2 (4th May 2017) - Liebrand, Janwillem; Udas, Pranita Bhushan
ABSTRACT: In this article, using the Department of Irrigation in Nepal as a case study, we argue that professional performance in irrigation engineering and water resources development is gendered and normalised as 'masculine'. In Nepal, the masculinity of professional performance in irrigation engineering is located in intersections of gender, class, caste, ethnicity, sexuality, nationality and disciplinary education, and hinders especially female engineers to perform as a 'normal' engineer. Our analysis is based on interviews with male and female engineers in the department, documentation research, and ethnographic observations in the period 2005–2011. Our study suggests that professional performances and engineering identities in the organisation have always been tied to performances of masculinity. This implies that career prospects in the Nepalese irrigation department for female engineers remain grim; because for them to succeed and belong, they have to reconcile the near incommensurable: a performance of a 'lady engineer' with that of a 'normal' engineer.